Análise da topologia de redes veiculares usando métricas de centralidade - Oliveira, Igor Marcos Araujo de (2019)
Vehicle networks are called VANET, in VANETs data propagation is one of the central themes in the search for efﬁciency in data transmission. Studies are being conducted to improve the quality of data transmission between vehicles, to investigate vehicle behavior on the road at certain time periods and to predict the best or shortest route, always with the aim of propagating data and strategizing the case. of connection failures. Thus the connection between vehicles is a barrier that can make the network objective impossible, preventing data from reachingits destinationin time to avoid,for example, a collision between automatavehicles. This paper seeks to analyze the topology of vehicular networks in the cities of Cologne, Germany, Madrid and Créteil in France, mapping them as complex networks for each collection time and extracting metric properties from graph theory and complex network ssuch as: Degree Medium, Clustering Coefﬁcient, Betweenness, Closeness, Diameter. The datas set is then applied to Hellinger’s stochastic quantiﬁer to evaluate changes between collection time points. In this sense, the evaluation indicates possible divergences between time periods that may justify potential problems in the network path, as well as the need for structural improvements. This work was based on the methodology that consisted of the followingsteps: I)network deﬁnition,II)network treatment,III)network characteristics treatment, IV) visual inspection. The results were numerically and graphically generated to allow the evaluation and behavioral interpretation of the studied networks based on the centrality measures and the stochastic quantiﬁer used in this work